2002
DOI: 10.1099/0022-1317-51-2-123
|View full text |Cite
|
Sign up to set email alerts
|

recA and glnA sequences separate the Bacteroides fragilis population into two genetic divisions associated with the antibiotic resistance genotypes cepA and cfiA

Abstract: The sequences of part of the glutamine synthetase-encoding gene ( glnA) and of the RecA-encoding gene (recA) were determined and aligned for 45 Bacteroides fragilis isolates from different clinical and geographical origin. The patterns of sequence divergence of glnA and recA were very similar. The sequences of a 303-bp fraction of recA showed 45 nucleotide substitutions, 40 of which allowed the separation of B. fragilis into two major divisions, which were not found when the deduced amino acid sequences were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
3
19
0
Order By: Relevance
“…Furthermore, CTn86 and CTn86-like elements were found exclusively in cepA-positive/cfiA-negative strains, and 95% of CTn9343 and CTn9343-like elements were also found in cepA-positive/ cfiA-negative strains. These results are in agreement with previous reports that found ETBF exclusively in cepA-positive/ cfiA-negative strains (10,11). These studies and others showed that cepA and cfiA never are in the same B. fragilis strain and that these genes are associated with distinct genetic divisions of B. fragilis: cepA is present only in division I and cfiA is present only in division II (10,11,25).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, CTn86 and CTn86-like elements were found exclusively in cepA-positive/cfiA-negative strains, and 95% of CTn9343 and CTn9343-like elements were also found in cepA-positive/ cfiA-negative strains. These results are in agreement with previous reports that found ETBF exclusively in cepA-positive/ cfiA-negative strains (10,11). These studies and others showed that cepA and cfiA never are in the same B. fragilis strain and that these genes are associated with distinct genetic divisions of B. fragilis: cepA is present only in division I and cfiA is present only in division II (10,11,25).…”
Section: Discussionsupporting
confidence: 83%
“…These studies and others showed that cepA and cfiA never are in the same B. fragilis strain and that these genes are associated with distinct genetic divisions of B. fragilis: cepA is present only in division I and cfiA is present only in division II (10,11,25). Due to the genetic distance observed between these two divisions by different genotyping approaches, it has been suggested that these divisions may represent different species (10,11,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen in Table 1, higher MIC values were observed for these antibiotics in strains where the cepA gene was detected than in strains 119 and AK-2 (cepA À ). Gutacker et al (2002) concluded that the â-lactamaseencoding genes cepA and cfiA were never found together in the same isolate. This apparent mutual exclusion may be explained by the acquisition of these genes in separate and unique events.…”
Section: Resultsmentioning
confidence: 99%
“…By using various molecular typing methods, such as arbitrarily primed PCR, ribotyping, multilocus enzyme electrophoresis, and sequencing of recA and glnA genes, cfiA-negative and cfiA-positive strains were shown to belong to two genotypically distinct groups (9,10,13). Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has the capacity to discriminate closely related species based on the spectrum of constantly expressed highly abundant proteins, such as ribosomal proteins.…”
mentioning
confidence: 99%